Assessment model for digital services provided by higher education institutions - Pasini, Ariel Cristian
This paper explores the concept of introducing digital government in higher education institutions (HEI), mainly universities. In particular, it introduces the concept of University Digital Government (UDG), proposes a classification of core university digital services (UD-services) offered by such institutions to their community members, and defines a maturity model for assessing university academic units in terms of the maturity level of their UD-services. The research work relies on case studies in Argentina. The model considers possible delivery channels for each type of service and based on the service and the channels, it defines the maximum level of maturity that could be reached. Based on an assessment of how services are delivered by academic units, a scale is established for measuring the status of UDG development in a given academic unit. The model was applied in nine universities in Argentina and the results obtained are discussed in the paper. The main contribution of the proposed model is to serve as a road map illustrating and guiding academic units in their efforts on applying digital technologies to improve the quality of their services.